Perceived family-supportive work culture, affective commitment and turnover intention of employees. - Ahmad, Aminah; Omar, Zoharah (2010)
The objective of this research is to examine the role of perceived family-supportive work culture in reducing turnover intention of employees and the mediating role of affective commitment in the relationship between perceived family-supportive work culture and turnover intention. The subjects in this study constituted 693 employees from 20 private service organizations in the Klang Valley, Malaysia. Results of multiple regression analyses indicate that perceived family-supportive work culture is positively related to turnover intention of employees and employees’ affective commitment mediate the relationship between perceived family-supportive work culture and turnover intention. The results imply the need for employers to understand how employees view the family-friendly programs in terms of the support provided and the values they place on the programs as captured in perceived family-supportive work culture. Positive perceptions would help reduce turnover intention as well the affective commitment of employees.